Effects on production of milking crossbred suckler cows grazing a semi-arid area of Kenya. III. Post-weaning growth of crossbred calves - Anindo, D.O.; Topps, J.H. (1993)
Three experiments were conducted in successive years on crossbred suckler cows on a farm in a semi-arid area close to Nairobi, Kenya. The cows were mated seasonally to calve approximately 1 month before the rainy season (March to May). The effects of milking once daily and supplementation (2 kg/head per day) was examined in a 2 X 2 factorial design by measuring the growth rate of the calves after weaning. In experiments 2 and 3, each of the 4 groups of calves was sub-divided to give equal numbers of calves either receiving or not receiving a small amount (<less or =>1 kg/day) of weaner pellets. In the 3 succeeding years, 32, 53 and 74 calves respectively were studied. Milking the suckled cows was the most important factor affecting growth rates and liveweights of calves post-weaning in the 3 experiments. Liveweights at 12 months of age were significantly lower (P<less or =>0.05) in calves from milked cows than in those from non-milked cows in all 3 experiments; a similar significant difference was observed at 15 months of age in experiment 1 and at 24 months of age in experiments 1 and 2. However, as the calves grew from weaning to the age of 15 or 24 months this difference became smaller. In experiment 1, the difference decreased from 49 kg at weaning to 12 kg at 24 months, while in experiment 3 the decrease was from 12 kg at weaning to 9 kg at 12 months. In experiment 2, a smaller difference at weaning was maintained. This decrease with age indicated that the calves that had been restricted by the amounts of milk obtained from the dam had exhibited compensatory growth. Provision of concentrate to the cow and/or the calf had only a small, not significant effect on the growth of the calf post-weaning. It was concluded that the withdrawal of milk from the crossbred cows had a relatively small effect on the performance of their calves post-weaning. Feeding of concentrates to the cows and calves had little effect on this performance, which was not worthwhile in terms of economy of use and biological efficiency.